OPTIMASI PROSES TURNING PADA AA 6061 DENGAN METODE MINIMUM QUANTITY LUBRICATION - Anshori, Mohammad; Sonief, Achmad As'ad; Setyarini, Putu Hadi (Jurnal Rekayasa Mesin, 2024)
The use of vegetable oil-based cutting fluids under minimum quantity lubrication (MQL) lubrication has been suggested as a potential alternative. The cutting fluid is conveyed in the form of fine droplets with compressed air delivered precisely to the cutting zone. This study aims to determine the effect of variations of rubber seed oil and coconut oil as a cutting fluid on the surface roughness of the machining process using the MQL method. Researchers used the parameters of cutting fluid flow rate of 120 ml/hour and 180 ml/hour, cutting speed of 500 rpm, feed rate of 0.011 mm/rev, depth of cut of 0.5 mm with variations of coconut oil 10%, 20%, 30%. The results showed that the lowest surface roughness value was at a flow rate of 180 ml/hour with a 30% variation of 0.886 µm, while the highest surface roughness value was at a flow rate of 120 ml/hour with a 10% variation of 1.164 µm, meaning that the greater the flow rate and variation cutting fluid results in a decrease in surface roughness, this is due to the influence of the addition of coconut oil, the more coconut oil is added, the surface roughness value decreases. The surface roughness value decreases as the viscosity decreases, because the viscosity of coconut oil is lower than that of rubber seed oil, so that the flow rate of the cutting fluid is able to work optimally to lubricate the contact area.